The Effect of a Medicinal Chinese Herb on Platelet Function - Wang, Z; Roberts, J M; Grant, P G; Colman, R W; Schreiber, A D (Thrombosis and Haemostasis, 1982)
We investigated the effect of the Chinese herb Injectio Salvia Miltiorrhizae (ISM) on human platelet function in vitro. ISM inhibited platelet aggregation and serotonin release induced by either ADP or epinephrine in a dose dependent manner. This effect of ISM was observed with both gel-filtered platelets (ID50 = 8–30 μg ISM/ml gel-filtered platelets) and platelets in plasma (ID50 = 400–900 μg ISM/ml of platelet-rich plasma). The active molecule(s) in ISM was heat stable, resistant to acid, base and proteolysis and fractionated on Sephadex 6-25 at MW ~ 280. ISM did not interact with the platelet α-adrenergic receptor, but increased cAMP in intact platelets. The results are consistent with the concept that ISM inhibition of platelet aggregation and release is mediated by an increase in platelet cAMP. The exact mechanism whereby ISM increases platelet cAMP appears to be that of inhibition of cyclic AMP phosphodiesterase. The effect of ISM on platelet function is one mechanism which might explain the therapeutic effect of ISM in experimental and clinical coronary artery disease.
Keywords: Injectio salvia miltiorrhizae (ISM); Platelet-rich plasma (PRP); Platelet aggregation; ADP and platelet cAMP